"FROZEN" CONFLICTS IN THE POST-SOVIET AREA AS A TOOL OF RUSSIAN INFLUENCE IN THE REGION (Вісник: Міжнародні відносини, 2024)
The collapse of the USSR in 1991 was accompanied by an escalation of armed conflict in the countries of the post-Soviet region, where the Russian authorities tried to maintain dominance with the help of such a proven tool of geopolitical influence as conflict management. Being unable to reconcile the warring parties, the Russian Federation usually pursues a policy of "freezing" them. Ethnopolitical conflicts in the Transnistrian region of Moldova, the Abkhaz and Tskhinvali regions of Georgia have been brought to such a state, in particular. Regarding Ukraine, against which the Russian Federation launched a war in 2014, the Kremlin seeks to "reset" its sovereign status, using tactics of "freezing" the conflict with the aim of further decomposition of the Ukrainian state into a new empire.M e t h o d s. The main methodological approaches to the study of "frozen conflicts" are historical, social and political. Such approaches made it possible to trace the dynamics of the development of conflicts in the post-Soviet space at various stages.R e s u l t s. The article examines the influence of the Russian Federation on the emergence and escalation of ethnopolitical conflicts in Azerbaijan, Armenia, Georgia and Moldova, as well as the reasons for the unprovoked armed aggression of the Russian Federation against Ukraine. It has been proven that the main geopolitical motive for the Kremlin's participation in the so-called "settlement" of ethnopolitical conflicts is the desire to get the world's leading states to recognize the post-Soviet space as Russia's "sphere of special responsibility." The author is convinced that the decisive factor in the "frozen conflicts" planned by the Kremlin is Russia's reluctance to get rid of the imperial syndrome.C o n c l u s i o n s. The author's analysis of the causes and consequences of "frozen conflicts" in the post-Soviet space showed that despite the significant contribution of the USA, the EU and the OSCE to conflict resolution, the Russian Federation seeks to play a leading role here. This allows it to significantly limit the European integration aspirations of the post-Soviet countries. However, the settlement of the Karabakh conflict between Azerbaijan and Armenia with the active participation of Turkey has changed the geopolitical balance of forces in the South Caucasus region and, together with a probable Ukrainian victory in the war with the Russian Federation, may stand in the way of the Kremlin's imperial ambitions.
Keywords: "frozen" conflicts, post-Soviet space, geopolitical interests, states of the former USSR, imperial syndrome